2017
DOI: 10.1186/s12879-017-2814-x
|View full text |Cite
|
Sign up to set email alerts
|

HIV serostatus knowledge and serostatus disclosure with the most recent anal intercourse partner in a European MSM sample recruited in 13 cities: results from the Sialon-II study

Abstract: BackgroundKnowledge of HIV status can be important in reducing the risk of HIV exposure. In a European sample of men-who-have-sex-with-men (MSM), we aimed to identify factors associated with HIV serostatus disclosure to the most recent anal intercourse (AI) partner. We also aimed to describe the impact of HIV serostatus disclosure on HIV exposure risks.MethodsDuring 2013 and 2014, 4901 participants were recruited for the bio-behavioural Sialon-II study in 13 European cities. Behavioural data were collected wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 32 publications
1
12
0
5
Order By: Relevance
“…These CRF outbreaks in PWIDS resulted in major public health responses by the Bulgarian Ministry of Health, including HIV prevention and education campaigns, which significantly reduced HIV diagnoses in this vulnerable population. However, despite significant efforts by public health programs and NGOs to provide educational and prevention campaigns, HIV continues to be a significant burden for MSM in Bulgaria and other European countries [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…These CRF outbreaks in PWIDS resulted in major public health responses by the Bulgarian Ministry of Health, including HIV prevention and education campaigns, which significantly reduced HIV diagnoses in this vulnerable population. However, despite significant efforts by public health programs and NGOs to provide educational and prevention campaigns, HIV continues to be a significant burden for MSM in Bulgaria and other European countries [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that ignorance of the serological status of an individual with HIV may contribute to HIV exposure. Thus, it is necessary to incorporate some strategies that can reduce such exposure, such as access to prevention methods, frequent use of condoms, routine HIV serological testing, and HIV/AIDS awareness) to reveal their diagnosis, particularly for the fixed partners (10)(11) .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Marcus et al [25] modelling the relationship between unprotected anal intercourse (UAI) and HIV disclosure with the same study dataset, found that among those respondents being aware of being HIV positive, condom use with steady partners was higher than among HIV negative men. However, condom use with non-steady partners was also lower.…”
Section: Discussionmentioning
confidence: 99%